Constitutionalism Review of the Extension of the Term of Office of the Village Head in Law Number 3 of 2024 - Elviani, Hikmah; Sunggara, M. Adistya; Abdillah, Junaidi (GoAcademica Research & Publishing, 2025)
This article aims to examine how the extension of the term of office of village heads in Law Number 3 of 2024 raises debates related to democracy and constitutionalism. This policy extends the term of office from six to eight years with a maximum of two terms, potentially inhibiting leadership regeneration and community political participation. From the perspective of constitutionalism, this policy can weaken checks and balances and increase the risk of abuse of authority. This research uses a normative juridical method by analyzing related regulations and a historical approach to trace the evolution of regulations. Data is obtained through document studies with descriptive-analytical analysis to assess the alignment of this policy with democratic principles. The results show that extending the term of office of the village head can reduce the accountability and transparency of the village government. A strict monitoring mechanism is needed so that this policy does not open a gap for abuse of power, as well as harmonization of regulations to ensure that village governance remains democratic and accountable.